The West-Palearctic species of the genus Tonnoiriella Vaillant, 1971 (Diptera: Psychodidae, Psychodinae) - Wagner, Rüdiger; Withers, Phil (Zootaxa, 2020)
Tonnoiriella Vaillant, 1971 was one of the genera not treated by F. Vaillant for his revision in Die Fliegen der paläartktischen Region. Here we provide a genus diagnosis, re-describe known species based mainly on type material, and provide descriptions and figures of the West-Palearctic species. New species described are T. aurasica sp. nov., T. italiae sp. nov., T. ikariae sp. nov., T. andradei sp. nov., T. rhodesica sp. nov., and T. goncalvesi sp. nov.; T. androsica Vaillant, 1978, T. orientalis Vaillant, 1978, and T. pallidipenis Vaillant, 1978 are nomina nuda; finally 21 species are known to date from Europe and North Africa. The ejaculatory apodeme (basiphallus) is asymmetric and bilobed, lobes are stacked; one or both lobes are connected with asymmetric, cross positioned (distiphallus) sclerites. Operating of the open–close mechanism of the aedeagus is explained. Information on larval ecology is provided and the systematic position of the genus is discussed.